Gestión administrativa y de servicios de la compañía de transporte de Taxis del Cantón La Maná año 2016 - Carpio Mendoza, Jennifer Cristina (2017)
The research project was carried out with the aim of proposing a model of administrative management and services for the benefit of the taxi companies in La Maná Canton, with this, we are aiming to solve the administrative problems that these companies have had , the main disadvantages of the companies is the lack of a management model of administration that directs the operations developed by these companies, in the research, we applied the methodology of deductive and analytical research, it allowed to describe the administrative facts of the companies, we also used the descriptive and bibliographic research, it made possible to understand that the information is available as theories, results, instruments and techniques used, the interview and surveys were used for the collection of information that provided prime results for the development of the management model, these data served as a source to perform a diagnostic situation of the administrative situation of the taxi companies, it show us that they have an inadequate organization, the service provided by the taxi drivers is considered as regular by the users. Once the weaknesses were identified, it was necessary to draw up a model of administrative management and services to provide solutions to the above mentioned problems, as a reference was took the model of EFQM (European Foundation for Quality Management) the same that has as its purpose to encourage the management of enterprises of total quality and achieve continuous improvement, at the end of the project, we proposed a format for evaluating the quality of administrative management of taxi companies, this model was developed under the nine components of the EFQM, as: leadership, policy and strategy, staffs, helpers and resources, process, results in clients, results in staff, results in society, performance of the organization.